(untitled) (Research, Society and Development, 2021)
Fractures of the face in children exhibit unique and differentiable characteristics, with individualized management from diagnosis, through treatment, to the preservation of the case. Such fractures can trigger significant consequences, such as deformities and facial impairment, having differentiation with the adult population, especially regarding anatomical and social issues. The main objectives in the treatment of facial fractures in pediatric patients are to restore functionality and provide bone union while preserving the potential for facial growth. When possible, a non-surgical approach should be indicated, but in cases that require surgical reduction and internal fixation, this treatment should be performed using less traumatic surgical technique. Long-term follow-up is recommended for an adequate assessment of the functionality and final aesthetics achieved. The objective of this work is to present the clinical case of a pediatric patient who developed a bilateral fracture of the jaw after an automobile accident, translated into a surgical form.